Dynamic path planning of UAV in three-dimensional complex environment based on interfered fluid dynamical system - Tamanakĳprasart, Komsun; Mondal, Sabyasachi; Tsourdos, Antonios (American Institute of Aeronautics and Astronautics (AIAA), 2024)
The difficulties of path planning for unmanned aerial vehicles (UAVs) grow with the increase of static obstacles. Moreover, the presence of dynamic obstacles piles up the computation burden, as the UAVs need to dynamically replan and compute a new path to avoid them within an expanding search space. Existing studies on dynamic path planning have primarily evaluated algorithms in low-fidelity simulations and focused on improving computational efficiency. Nonetheless, these efforts remain insufficient for practical applications due to the limited computing powers of onboard processors, coupled with the significantly more cluttered nature of real-world environments. This paper introduces a dynamic autorouting program featuring the Interfered Fluid Dynamical System (IFDS) for adaptive path planning and a novel safeguarding function to ensure safety distances during obstacle avoidance. The proposed strategy brings a dynamic path planning framework, allowing UAVs to adaptively reroute to avoid areas and obstacles that will change throughout the flight in complex environments.